Answer:
see below
Step-by-step explanation:
(3x+1)/2<−x+4
Multiply each side by 2 using the multiplication property of equality
3x+1 < -2x +8
Subtract 1 from each side using the subtraction property of equality
3x < -2x+7
Add 2x to each side using the addition property of equality
5x < 7
Divide each side by 5 using the division property of equality
x < 7/5
Step-by-step explanation:
factor 4 out of the variable terms, as this helps.
but my approach is simply to define the target and then calculate "backwards".
we want to find
(ax + b)² = a²x² + 2abx + b²
and now we compare with the original equation :
a²x² = 4x²
a² = 4
a = 2
2abx = 16x
2×2×bx = 16x
4b = 16
b = 4
b² = 16, but we have only 3, so we need to subtract 16-3 = 13 from the completed square.
so, our equation is
(2x + 4)² - 13 = 0
(2x + 4)² = 13
2x + 4 = sqrt(13)
2x = sqrt(13) - 4
x = sqrt(13)/2 - 2
Answer:.42
Step-by-step explanation:
You could do a few (3-4)milk carton